SEARCH FOR THE STANDARDS OF THE EUROPEAN UNION CHARTER OF FUNDAMENTAL RIGHTS - Žaltauskaitė-Žalimienė, Skirgailė (Teisė, 2016)
As regards the legal content of the Charter, it should be noted that it does not implement fundamental rights that are absolutely new. The content and extent of the fundamental rights, once again reaffirmed in the Charter, arise from constitutional traditions and international obligations common to all Member States, including the ECHR, the case law of the CJEU and the European Court of Human Rights. National courts face difficulties resulting from the application and assurance of the fundamental rights at different levels, i.e. by the Charter, the ECHR, national constitutions and finally by the concept of the fundamental rights as general principles of Union law. Although the European and national concepts of fundamental rights are based on common legal traditions and have to be presumed as compatible, in judicial practice the question arises as to which level a national court has to comply with, or whether the court has to follow the system of fundamental rights that ensures the highest protection of fundamental rights? The Melloni judgment suggests that a national court does not have the right to apply the system that is the most favourable to the person, but has to observe the EU standards of fundamental rights. In practice many national court use the Charter in three main possible ways: as a source of interpretation of national law, direct application of the Charter provisions, and as a means to verify the arguments of the parties to the proceedings. It has to be noted also that in all three cases the Charter may be referred or applied by national courts far beyond the scope of its application, i.e. not necessarily in the field of the application of the EU law or national legislation implementing the latter. These features are also characteristic to the jurisprudence of Lithuanian national courts, in particular the Supreme Administrative Court. Taking them into account, it can be suggested that national courts should refer more often to the Charter as a source of inspiration and the standard of a good practice even in situations not covered by the EU law, unless there is no higher national standard for the protection of fundamental rights.